Skeletal Muscle Depletion Predicts the Prognosis of Patients With Hepatocellular Carcinoma Treated With Radiotherapy - Lee, Joongyo; Cho, Yeona; Park, Sangjoon; Kim, Jun Won; Lee, Ik Jae (Frontiers in Oncology, 2019)
Background: Sarcopenia is gaining attention as a poor prognostic factor for various types of malignancies. This study evaluated the prevalence and prognostic significance of sarcopenia and its association with survival in hepatocellular carcinoma (HCC) patients who underwent radiotherapy (RT) to the primary site. Materials and Methods: Between January 2009 and November 2016, 156 patients with HCC that underwent RT to the liver were retrospectively studied. Sarcopenia was defined as an L3 skeletal muscle index of <49 cm2/m2 for men and <41 cm2/m2 for women as proposed by Korean-specific cut-off value. Sarcopenia was identified pre- and post-RT (within 3 months from the end of RT). Results: Pre-RT sarcopenia occurred in 99 (63.5%) patients and was significantly associated with higher levels of protein induced by vitamin K absence or antagonist-II (PIVKA-II), lower percentage of overweight/obesity (body-mass index), higher percentage of previous systemic chemotherapy, and lower total RT dose. At a median follow-up of 9.3 months, median overall survival (OS) was significantly lower in patients with pre-RT sarcopenia than in those without (7.1 vs. 15.3 months, p<0.001). In multivariate analysis (reporting hazard ratio [HR]: 95% confidence interval [CI]), albumin-bilirubin score (2.35: 1.33-4.17; p=0.003), total dose (0.44: 0.27-0.71; p=0.001), and pre-RT sarcopenia (2.38: 1.53-3.70; p<0.001) were independent OS prognostic factors. Among patients without pre-RT sarcopenia, 20 newly developed sarcopenia after RT and showed significantly lower OS compared to those without sarcopenia after RT (n=35) (median 14.1 vs. 17.5 months, p=0.018). Multivariate logistic regression analysis (reporting odds ratio [OR]) demonstrated older age (310.190; p=0.007), Child-Pugh classification B or C (15.239; p=0.047), higher alpha-fetoprotein (128.486; p=0.008), higher PIVKA-II (118.536; p=0.027), and larger planning target volume (51.310; p=0.026) as significant factors for newly developed post-RT sarcopenia. Conclusion: Newly developed sarcopenia after RT, as well as pre-RT sarcopenia, were associated with poor survival for HCC patients who underwent RT to the liver. This result suggests the possibility that early intervention such as nutritional support and exercise therapies before and during RT could prevent muscle wasting and may be effective in improving the prognosis of HCC patients.